New evidence from plasma ceramides links apoE polymorphism to greater risk of coronary artery disease in Finnish adults - Karjalainen, Juho-Pekka (J Lipid Res, 2019)
apoE, a key regulator of plasma lipids, mediates altered functionalities in lipoprotein metabolism and thus affects the risk of coronary artery disease (CAD). The significance of different apoE polymorphisms remains unclear; although the ε4 allele is clearly associated with increased cholesterol levels (which inform CAD risk), direct studies about apoE polymorphisms on CAD risk and development have yielded controversial results. Furthermore, certain species of ceramides—complex lipids abundant in plasma LDL—are markers of increased risk of myocardial infarction and cardiovascular death. Using a high-throughput MS approach, we quantified 30 molecular plasma ceramide species from a cohort of 2,160 apoE-genotyped (rs7412, rs429358) young adults enrolled in the population-based Cardiovascular Risk in Young Finns Study. We then searched this lipidome data set to identify new indications of pathways influenced by apoE polymorphisms and possibly related to CAD risk. This approach revealed a previously unreported association between apoE polymorphism and a consistently documented high-risk CAD marker, Cer(d18:1/16:0). Compared with the apoE ε3/3 reference group, plasma levels of apoE ε4 were elevated and those of apoE ε2 were lowered in all subjects without evidence of apoE-by-sex interactions. apoE associated with seven ceramides that are connected to atherogenically potent macrophages and/or lipoprotein particles; these associations could indicate a plausible linkage between apoE polymorphism and ceramide metabolism, leading to adverse plasma LDL metabolism and atherogenesis. In conclusion, new evidence from plasma ceramides links apoE polymorphism with an increased risk of CAD and extends our understanding of the role of apoE in health and disease.